2020
DOI: 10.1088/1757-899x/830/3/032001
|View full text |Cite
|
Sign up to set email alerts
|

HR analytics: Employee attrition analysis using logistic regression

Abstract: Employee attrition can become a serious issue because of the impacts on the organization’s competitive advantage. It can become costly for an organization. The cost of employee attrition would be the cost related to the human resources life cycle, lost knowledge, employee morale, and organizational culture. This study aimed to analyze employee attrition using logistic regression. The result obtained can be used by the management to understand what modifications they should perform to the workplace to get most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Konuya ilişkin yapılan çalışmalara bakıldığında; ilgili konunun demografik değişkenler (Nagadevara, 2015;Setiawan, 2019;Najafi-Zanganeh vd., 2021); çalışan yıpranmasına sebep olan faktörler (Raza vd., 2022); çalışan yıpranmasının nedenleri (Firth vd., 2014;Falluchi vd., 2020;Negi, 2013;Thariq ve Mahideen, 2014;Kaur vd., 2019); yıpranma oranı (Usha ve Balaji, 2021;Dutta Burcu YİĞİT [2904] vd., 2020Ho vd., 2010); çalışan yıpranmasının olumsuz etkileri (Dobhal ve Nigam, 2018;Bacha, 2016) konuları ile çalışıldığı görülmüştür. Gelecek yıllarda ulusal alanda da bu çalışmaların artması beklenebilir.…”
Section: Sonuç Ve öNeri̇lerunclassified
“…Konuya ilişkin yapılan çalışmalara bakıldığında; ilgili konunun demografik değişkenler (Nagadevara, 2015;Setiawan, 2019;Najafi-Zanganeh vd., 2021); çalışan yıpranmasına sebep olan faktörler (Raza vd., 2022); çalışan yıpranmasının nedenleri (Firth vd., 2014;Falluchi vd., 2020;Negi, 2013;Thariq ve Mahideen, 2014;Kaur vd., 2019); yıpranma oranı (Usha ve Balaji, 2021;Dutta Burcu YİĞİT [2904] vd., 2020Ho vd., 2010); çalışan yıpranmasının olumsuz etkileri (Dobhal ve Nigam, 2018;Bacha, 2016) konuları ile çalışıldığı görülmüştür. Gelecek yıllarda ulusal alanda da bu çalışmaların artması beklenebilir.…”
Section: Sonuç Ve öNeri̇lerunclassified
“…Bennett et al (1993) used hierarchical regression analysis to conclude that employee turnover is impacted to a great extent by employee bene ts while controlling the factors namely rm characteristics, rm setting, and workforce characteristics. Setiawan et al (2020) predicted the employee attrition level using logistic regression which included the number of companies worked, total years of work, years spent with the current manager, business travel frequency, and job satisfaction to name a few. In another conference, the different machine learning algorithms were compared with arch other after data collection through a survey and it was found that employee pride in working, security in the job, promotion, work-life balance, recognition…”
Section: Findings From Literaturementioning
confidence: 99%
“…I Setiawan [4,5] et al, designed a Employee attrition analysis using logistic regression. This system considers the dataset that describes the number of employees, leaving organization every year.…”
Section: Related Workmentioning
confidence: 99%